2008
DOI: 10.1101/sqb.2008.73.055
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent Islet-1 Cardiovascular Progenitors in Development and Disease

Abstract: During the past several years, advances at the intersection of cardiovascular development and heart stem cell biology have begun to reshape our view of the fundamental logic that drives the formation of discrete tissue components in the mammalian heart. Although many of the critical genes that control cardiac myogenesis have been identified, our understanding of how a highly diverse and specialized subset of heart cell lineages arises from mesodermal precursors and is subsequently assembled into distinct muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 117 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…Various types of congenital heart disease can be caused by Islet-1 insufficiency (14,15,29). Islet-1 has also been recognized as a marker of cardiovascular progenitors (16,30). Islet-1-positive progenitors can differentiate into diverse cardiovascular cell lineages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of congenital heart disease can be caused by Islet-1 insufficiency (14,15,29). Islet-1 has also been recognized as a marker of cardiovascular progenitors (16,30). Islet-1-positive progenitors can differentiate into diverse cardiovascular cell lineages.…”
Section: Discussionmentioning
confidence: 99%
“…However, Islet-1, a subtype of the LIM-homeodomain transcription factor (LIM-HD) subfamily, contains a DNA binding site and two LIM domains, and is able to bind with GCN5, which is a member of the HAT family involved in cardiomyocyte, hepatocyte, as well as bone and neuron differentiation (1214). Several studies have demonstrated that Islet-1 is crucial to cardiac development and cardiomyocyte differentiation (1516). Thus, we hypothesized that Islet-1 is a key factor during the process of the specific differentiation of MSCs into cardiomyocyte-like cells and that it exerts its effects possibly through modifications in histone acetylation and deacetylation.…”
Section: Introductionmentioning
confidence: 99%
“…Timing is also relevant to our appreciation of the etiologies of congenital heart defects in humans given the importance of sequential differentiation of the first heart field (FHF) and the second heart field (SHF) (Bruneau, 2008; Nakano et al, 2008; Srivastava and Olson, 2000). Nkx2-5 is expressed in FHF and SHF of mouse and zebrafish embryos (Guner-Ataman et al, 2013; Stanley et al, 2002) and mutations in both lineages result in CHD (Lyons et al, 1995; Prall et al, 2007; Tanaka et al, 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…Mesp1 is a bHLH transcription factor that emerges in the early embryo within the nascent mesoderm, most prominently in precardiac tissue, and is proposed to play a key role in the cardiac lineage specification [36][37][38]. Islet1 is considered the defining marker of progenitor cells in the secondary heart field [39,40], although more recent data indicated that islet1 is also exhibited by progenitors within the primary heart field [41,42].…”
Section: Introductionmentioning
confidence: 99%